Drivers of human–black caiman (Melanosuchus niger) conflict in Indigenous communities in the North Rupununi wetlands, southwestern Guyana - Pierre, MA; Jacobsen, KS; Hallett, MT; Harris, A-EM; Melville, A; Barnabus, H; Sillero-Zubiri, C (Wiley, 2022)
Recovering populations of large carnivores impact the people that live alongside them, sometimes leading to conflict and lethal retaliation. One such carnivore, the black caiman (Melanosuchus niger) has been implicated in the destruction of fishing equipment, depredation of livestock and pets, and attacks on humans. In order to understand how various stakeholder groups are affected by the negative impacts of living alongside caiman, and their resulting attitudes and behaviors towards caiman, we conducted semistructured interviews in seven Indigenous communities in southwestern Guyana from November 2017 to October 2019. We used logistic and ordinal regression to identify demographic indicators of fishing behavior and factors that are associated with negative attitudes and antagonistic behavior. Loss of pets in addition to an effect of gender, rather than competition overfishing resources (as hypothesized) may drive conflict between Indigenous communities and black caiman. We propose site differences, such as ecotourism may affect attitudes about and behavior towards caiman. The presence of impacts on communities and retaliatory behavior indicates that human–wildlife and wildlife–human impacts involving black caiman may be a concern for the recovery of the species' populations, and the communities that coexist with them.